2007
DOI: 10.1295/polymj.pj2006201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structure of Bridging Group on Curing and Properties of Bisphenol-A Based Novolac Epoxy Resins

Abstract: ABSTRACT:Three bisphenol-A based novolac epoxy resins with different bridging groups: methylene, methinephenyl and methine-naphthyl, respectively, between bisphenol-A phenyl rings were prepared to study the effect of structure of bridging group on curing and properties of the epoxy resins. The structures of the obtained epoxy resins were characterized using FT-IR and 1 H NMR spectra, the molecular weight and polydispersity index were determined using GPC. The effect of bridging groups on the curing kinetics, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…To prepare bisphenol A-based novolacs, unlike the previous report, 6 2-methoxyethanol was utilized as a reaction solvent because it was expected to be a good solvent for the hydroxyl group-containing substrate, propagation species and products. Addition-condensation of bisphenol A with benzaldehyde (feed ratio = 1:2) was carried out.…”
Section: Synthesis Of Bisphenol a Novolacsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prepare bisphenol A-based novolacs, unlike the previous report, 6 2-methoxyethanol was utilized as a reaction solvent because it was expected to be a good solvent for the hydroxyl group-containing substrate, propagation species and products. Addition-condensation of bisphenol A with benzaldehyde (feed ratio = 1:2) was carried out.…”
Section: Synthesis Of Bisphenol a Novolacsmentioning
confidence: 99%
“…From this viewpoint, bisphenol A novolac is expected to reveal unique properties which are different from phenol novolac. 5 Previously, Pan et al reported addition-condensation of bisphenol A with formaldehyde or aromatic aldehydes; 6 however, the preparation of bisphenol A-based novolacs with high molecular weights was not achieved (M n : ca. 800, M w =M n : ca.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic resins [1][2][3][4][5][6][7][8][9][10] and related polymers [11][12][13][14][15][16][17][18][19][20][21][22] are a very important class of common organic polymers, and have numerous applications in the development of materials [1][2][3][4][5][6] such as thermosetting resins, adhesives, photoresists and polymer composites. The main characteristics of phenolic resins, such as heat stability and mechanical properties, are attributed to their rigid rod-like polymer backbone of poly(phenylenemethylene).…”
Section: Introductionmentioning
confidence: 99%
“…These resins have interesting properties that make them suitable for industrial use, such as thermostability and mechanical strength. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] During the curing of novolacs, hexamethylenetetramine (HMTA) is frequently used as the curing agent; 1 however, the resultant curing products usually tend to contain amine derivatives and the unreacted curing agent as impurities, which often lead to coloration and degradation of the products.…”
mentioning
confidence: 99%